Knowledge, Attitude and Practice towards Female Condom Use at International Paramedical Institute-Maya, Wakiso District. A Cross-sectional Study. - Watmon , Erick (Student’s Journal of Health Research Africa, 2022)
Background: Sexually transmitted infections especially HIV/AIDS and unwanted pregnancy among students in higher institutions and universities is now a problem yet condom offers protection against sexually transmitted infections including HIV and pregnancy. Despite various promotions, female condom use remains relatively low among students, especially girls. This study purposed to assess the knowledge, attitude, and practice toward female condom use among females of the International Paramedical Institute, Wakiso District Uganda. Methodology: A descriptive cross-sectional study was implemented and a cluster sampling method was adopted to obtain the required number of respondents bringing up to 100 respondents which were got from 134 sample sizes. Results: The results of this study shows that of 100 respondents majority had the good and proper knowledge of female condom and 69(69%) of the respondents agreed that female condom can protect against HIV/AIDS. Regarding attitude toward the use of female condoms, most respondents have a negative attitude as 66(66%) of the respondents agreed that using female condoms reduces sexual pleasure and 84% agreed that FC makes sex uncomfortable. The level of female condom use was as low as only 11(11%) of the respondents. Conclusion; This study, therefore, concludes that the majority of females have does not have a good attitude and does not use female condoms despite having good knowledge of female condom, the level of use is very minimal and irregular. Recommendation: This study, therefore, recommends that for consistent and regular use of a female condom, there is a need to provide better information on a female condoms and make female condoms available and easily accessible to students in various places including hospitals. Better information can be achieved by the introduction of sex education in institutions and universities.